resolva as equações do 2 º grau ,reduzindo os termos semelhantes:
a) (x-1).(x-2)=6
b) x(x-2)=2.(x=6)
c)(x-2)²=3x+4
Soluções para a tarefa
Respondido por
1
a) (x-1).(x-2)=6
x² - 2x - x + 2 = 6
x² - 3x + 2 - 6 = 0
x² - 3x - 4 = 0
a = 1 b = - 3 c = - 4
Δ = b² - 4.a.c
Δ = (- 3)² - 4.(1).(- 4)
Δ = 9 + 16
Δ = 25
x = - b ± √Δ
2.a
x = - (- 3) ± √25
2.1
x = + 3 ± 5
2
x = 3 + 5 = 8 = 4
2 2
x = 3 - 5 = - 2 = - 1
2 2
S[- 1, 4]
b) x(x-2)=2.(x=6)
x² - 2x = 2x + 12
x² - 2x - 2x - 12 = 0
x² - 4x - 12 = 0
a = 1 b = - 4 c = - 12
Δ = b² - 4.a.c
Δ = (- 4)² - 4.(1).(-12)
Δ = 16 + 48
Δ = 64
x = - b ± √Δ
2.a
x = - (- 4) ± √64
2.1
x = + 4 ± 8
2
x = 4 + 8 = 12 = 6
2 2
x = 4 - 8 = - 4 = - 2
2 2
S[- 2, 6]
c)(x-2)²=3x+4
x² - 4x + 4 = 3x + 4
x² - 4x - 3x + 4 - 4 = 0 elimina +4 - 4
x² - 7x = 0
x.(x - 7) = 0
x = 0
(x - 7) =
x - 7 = 0
x = + 7
S[0 ; 7]
x² - 2x - x + 2 = 6
x² - 3x + 2 - 6 = 0
x² - 3x - 4 = 0
a = 1 b = - 3 c = - 4
Δ = b² - 4.a.c
Δ = (- 3)² - 4.(1).(- 4)
Δ = 9 + 16
Δ = 25
x = - b ± √Δ
2.a
x = - (- 3) ± √25
2.1
x = + 3 ± 5
2
x = 3 + 5 = 8 = 4
2 2
x = 3 - 5 = - 2 = - 1
2 2
S[- 1, 4]
b) x(x-2)=2.(x=6)
x² - 2x = 2x + 12
x² - 2x - 2x - 12 = 0
x² - 4x - 12 = 0
a = 1 b = - 4 c = - 12
Δ = b² - 4.a.c
Δ = (- 4)² - 4.(1).(-12)
Δ = 16 + 48
Δ = 64
x = - b ± √Δ
2.a
x = - (- 4) ± √64
2.1
x = + 4 ± 8
2
x = 4 + 8 = 12 = 6
2 2
x = 4 - 8 = - 4 = - 2
2 2
S[- 2, 6]
c)(x-2)²=3x+4
x² - 4x + 4 = 3x + 4
x² - 4x - 3x + 4 - 4 = 0 elimina +4 - 4
x² - 7x = 0
x.(x - 7) = 0
x = 0
(x - 7) =
x - 7 = 0
x = + 7
S[0 ; 7]
Perguntas interessantes